Risk assessment for cardiovascular adverse drug events in the ICU: Case study on COVID-19 patients - Natalia L. Freitas; Raiane Diniz Oliveira; Ana Katarina da Silva Santos; Marcilio Cunha-Filho; Patricia Medeiros-Souza (PLoS ONE, 2026)
The COVID-19 outbreak quickly became a pandemic. In Brazil, more than seven million cases were recorded in 2020. Most patients affected by the disease were admitted to intensive care units (ICU), requiring qualitative polypharmacy, increasing the risk of serious adverse drug reactions (ADE), especially cardiovascular. This study aimed to identify cardiovascular ADE in the ICU of a reference hospital for the treatment of COVID-19 in Brasília, Brazil. The Tisdale score was determined by analyzing 141 medical records of patients with COVID-19 admitted in 2020. Furthermore, the MedUTI software was used to simulate hypothetical drug substitutions to reduce cardiovascular risk. The result showed that after simulating the hypothetical intervention of prescriptions, a 53% decrease in high-risk patients was observed (from 96.0% to 43.0%). In this optimized prescription condition, 56% of them began to show a Tisdale score of medium or low risk. In addition, a decrease from 67 to 51 of medications with serious cardiovascular ADE was noted, i.e., QT interval prolongation (from 37 to 30), Torsades de Pointes (from 21 to 15), and SS (from 9 to 6). The COVID-19 medical emergency has highlighted the need for rapid medication management in ICU patients. Thus, the use of technologies to support healthcare professionals’ work can be decisive for patient survival, especially in ICU overcrowding scenarios.